2012
DOI: 10.1017/s1598240800008043
|View full text |Cite
|
Sign up to set email alerts
|

Japan Under the DPJ: The Paradox of Political Change Without Policy Change

Abstract: In 2009, the Democratic Party of Japan (DPJ) brought an end to the long reign of the Liberal Democratic Party (LDP). However, despite high expectations, this politically transformative event has not unleashed significant policy change in Japan. We highlight five electoral factors that have acted as important constraints on policy change under DPJ rule. First, majoritarian electoral rules have led to a convergence in the policy positions of the two major political parties. Second, as the parties' policy positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…5 Such factors undoubtedly played a role in muddling the decisionmaking process of the DPJ once in office. However, in this article, I analyze the DPJ's transportation policies from a broader perspective, focusing on political changes over the past two decades (Lipscy and Scheiner 2012) and historical patterns of Japanese transportation policymaking.…”
Section: Since the Early 2000s The Democratic Party Of Japan (Dpj) Hasmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Such factors undoubtedly played a role in muddling the decisionmaking process of the DPJ once in office. However, in this article, I analyze the DPJ's transportation policies from a broader perspective, focusing on political changes over the past two decades (Lipscy and Scheiner 2012) and historical patterns of Japanese transportation policymaking.…”
Section: Since the Early 2000s The Democratic Party Of Japan (Dpj) Hasmentioning
confidence: 99%
“…DPJ transportation policymaking has been constrained by two additional factors attributable to the evolution of Japanese politics over the past two decades (Lipscy and Scheiner 2012). First, in recent years, the policy positions of the LDP and DPJ have moved toward convergence, motivated by an electoral system that emphasizes the preference of the median voter (Scheiner 2012;McElwain 2012).…”
Section: Since the Early 2000s The Democratic Party Of Japan (Dpj) Hasmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggesting they are include Reed, Scheiner, and Thies (2012), who found that their support bases began to converge after 2005 and valence considerations such as competence became important determinants of electoral victory; Scheiner (2012), who found that they discussed more of the same issues in Amy Catalinac 2009than in 2003and Dalton and Tanaka (2007), who found that voters perceived them to be closer in 2004 than in 1996. Indirect evidence is also found in the absence of conspicuous policy changes following the Democratic Party of Japan's (DPJ's) landslide victory in 2009 (e.g., Lipscy and Scheiner 2012;Hughes 2012). Studies implying divergence, however, include Sasada, Fujimura, and Machidori (2013), who document polarization in their roll-call votes after 2000; Taniguchi (2006), who finds considerable differences in their policy preferences; Shinoda (2009), who finds evidence of pre-election parliamentary confrontation between them; and Winkler (2013), who finds that candidates of the Liberal Democratic Party (LDP) shifted to the ideological right in recent years.…”
mentioning
confidence: 99%
“… Ibid. ; Phillip Y. Lipscy and Ethan Scheiner, “Japan under the DPJ: The Paradox of Political Change without Policy Change,” Journal of East Asian Studies , 12‐3 (2012), pp. 313–317; Aurelia George Mulgan, op.…”
mentioning
confidence: 99%